Comparative Study of Community Tourism Development Models in Baluran, Situbondo, and Banyuwangi National Parks - Mou’idhotul Hasana; Abdur Razak (Politeknik Siber Cerdika Internasional, 2025)
Background: Baluran National Park, located in Situbondo and Banyuwangi Regencies, is a strategic area for examining community-based tourism (CBT) development. Different tourism governance models adopted by the two regions result in varying levels of community participation, technological integration, and institutional readiness, which influence the effectiveness of sustainable CBT implementation. Aims: This study aims to examine and compare community-based tourism development models implemented in two strategic areas, namely Baluran National Park in Situbondo Regency and Banyuwangi Regency, with a focus on community capacity-building efforts and local community participation. Methods: This study employs a qualitative approach using a literature review method. Data were collected from various scientific journal articles and relevant academic literature related to community-based tourism, regional tourism governance, and sustainable tourism development. Result: The findings indicate significant differences in tourism development approaches as reflected in regional regulations. Situbondo Regency tends to emphasize the strengthening of local outputs as the foundation of tourism development, while Banyuwangi Regency demonstrates a stronger focus on institutional integration and managerial innovation. These differing approaches influence the level of community readiness and the effectiveness of CBT implementation in each region. Conclusion: This study concludes that policy harmonization between regions and the enhancement of local community capacity are essential foundations for achieving sustainable community-based tourism development in the Baluran National Park area. Adaptive governance strategies that align with local social and institutional conditions are necessary to optimize community participation and long-term tourism sustainability.